KEKUATAN HUKUM PERJANJIAN SEWA MENYEWA LAHAN PERTANIAN TANPA DASAR PERJANJIAN TERTULIS - Samsul Arifin; Afrowi (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The problem of legal planning in the sale of farmland is often disregarded. Generally speaking, the legal planning problem arising in the lease agreement for lease of agricultural land without the basis is the legal force of the agreement. Therefore, the role of legal engineering becomes essential in identifying the weaknesses and challenges of legal planning that may arise from lease agreements lease without the basis of a written agreement. The purpose of this study is to clarify and analyse the rights and obligations of the parties involved in a lease contract without the basis of a written agreement to see how the legal force of such an agreement. Qualitative descriptive methods are used to gather information from primary and secondary sources about the legal nature of a lease contract without the basis of a written agreement. These findings suggest that the legal force of a lease agreement leases without the basis of a written agreement depends on the relevant legal aspects. Thus, it has been known that a lease agreement leases without the basis of a written agreement has a fairly strict legal force in Indonesian law. The purpose of this research is to know the legal force of the lease agreement for lease of agricultural land without the basis of a written agreement and the implementation of the rental agreement to lease agricultural lands according to the Code of Civil Procedure Law.